Physical properties of the Algol-type eclipsing binary AO ser - N. Chehlaeh (2018)
© Published under licence by IOP Publishing Ltd. We present the results of a combined analysis of photometric time series and spectroscopic observations for the semi-detached eclipsing binary AO Ser aimed to study physical parameters of the system. New CCD photometric light curves in the B and V bands and radial velocities of AO Ser are presented. The Wilson-Devinney technique was used to simultaneously analyze the light and radial velocity curves for determining a new set of the system's parameters. The solution shows that AO Ser is a semi-detached eclipsing binary system with a mass ratio of 0.183 ± 0.003, an inclination of 89.42 ± 0.04 degrees and a secondary star's temperature of 4900 K.